What is nature conservation for the Portuguese public? Understanding the commonsensical image of nature to engage the general public in conservation efforts and to improve the communication between science and society - Vieira Da Silva, Carina (2019)
The protection of nature and biodiversity has been gaining importance in public opinion. Nevertheless, the implementation of conservation policies has experienced some public resistance, along with low levels of public involvement. This lack of public interest in and support to conservation may be related to citizens’ images of nature. In this article, we examine the commonsensical image of nature and its conservation according to two dimensions: cognitive beliefs and normative ethics. This image of nature was examined through a series of focus-group discussions with members of the general public in the Lisbon Metropolitan Area – Portugal and reflects the commonsensical perceptions of what nature conservation is. The results suggest that, although the participants were not familiar with scientific terminology, they hold rich, mental and social representations about nature and biodiversity. We present a conceptual framework that reflects participants’ overall image of nature as the basis of human life and, above all, as a source of multiple goods that ensure human beings’ survival, which characterizes the common-sense view of nature as largely anthropocentric. Our work provides policy-makers, planners and managers with a framework that reflects lay people’s perceptions of nature and biodiversity conservation that are instrumental in identifying conservation priorities, appropriate goals and suitable measures while ensuring communication between science and society.